2017
DOI: 10.1016/j.egypro.2017.07.408
|View full text |Cite
|
Sign up to set email alerts
|

Towards a new model of light quality assessment based on occupant satisfaction and lighting glare indices

Abstract: This study looks at the effect of daylighting on human performance. It includes a focus on glare index combined with the actual feeling of users of the classroom as a way to assess indoor lighting quality. The main objective of this research is to understand the impact of daylighting from windows on the glare sensation and also to determine which glare index is the closest to human visual sensation under local daylighting conditions in Biskra, Algeria with highly luminous climate. The study used High Dynamic R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 9 publications
0
3
0
2
Order By: Relevance
“…Several studies have shown that proper indoor daylighting has positive psychological and physiological effects on human beings and improves the productivity of office workers [1][2][3]. An appropriate visual environment in office rooms is, therefore, of utmost importance for several reasons.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that proper indoor daylighting has positive psychological and physiological effects on human beings and improves the productivity of office workers [1][2][3]. An appropriate visual environment in office rooms is, therefore, of utmost importance for several reasons.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, many analyses on visual comfort and the effects of lighting seem to be based on surveys/interviews rather than measuring the illuminance levels [5,6,11,12,15]. Even those works that reflect lighting measurements include surveys [13,16,24,25], adding subjective (and statistical) factors to the study.…”
Section: Introductionmentioning
confidence: 99%
“…This is a quite direct and simple technique that allowed a first evaluation of a quite relevant problem. However, it is somehow limited when compared to High Dynamic Range (HDR) imaging technology [24,25,34,35], as it does not give other interesting variables such as glare.…”
Section: Introductionmentioning
confidence: 99%
“…Estudos sobre o tema geralmente englobam ocupantes estáticos (WIENOLD, 2009), na contramão do dinamismo das pessoas e da visão em situações reais. Devido às múltiplas variáveis que envolvem a avaliação de conforto visual, as técnicas e os equipamentos usados nos estudos experimentais também são diversos (VIEIRA DIAS et al, 2017;YACINE et al, 2017). Esses estudos são fonte de valiosas informações referentes ao comportamento dos usuários as quais, ao não poderem ser obtidas através de simulações computacionais, lhes atribuem grande valor.…”
Section: Introductionunclassified